The interval between Ins2 and Ascl2 is dispensable for imprinting centre function in the murine Beckwith-Wiedemann region - Lefebvre, Louis (2009)
Imprinted genes are commonly clustered in domains across the mammalian genome, suggesting a degree of coregulation via long-range coordination of their monoallelic transcription. The distal end of mouse chromosome 7 contains two clusters of imprinted genes within a ~1 Mb domain. This region is conserved on human 11q15.5 where it is implicated in the Beckwith-Wiedemann syndrome. In both species, imprinted regulation requires two critical cis-acting imprinting centres, carrying different germline epigenetic marks and mediating imprinted expression in the proximal and distal sub-domains. The clusters are separated by a region containing the gene for tyrosine hydroxylase (Th) as well as a high density of short repeats and retrotransposons in the mouse. We have used the Cre-loxP recombination system in vivo to engineer an interstitial deletion of this ~280-kb intervening region previously proposed to participate in the imprinting mechanism or to act as a boundary between the two sub-domains. The deletion allele, Del(7AI), is silent with respect to epigenetic marking at the two flanking imprinting centres. Reciprocal inheritance of Del(7AI) demonstrates that the deleted region, which represents more than a quarter of the previously defined imprinted domain, is associated with intrauterine growth restriction in maternal heterozygotes. In homozygotes, the deficiency behaves as a Th null allele and can be rescued pharmacologically by bypassing the metabolic requirement for TH in utero. Our results show that the deleted interval is not required for normal imprinting on distal Chr 7 and uncover a new imprinted growth phenotype.